Solving Linear equations
1) -6y+2=-2(4y+3)
2) 14x-5=7+12x
3) -2(2x-3)=3x
4) -2(x-6)-5=7
5) 2-4(a+1)=8+a
6) 2/7x+6/7=-6/7
NO RUDE COMMENTS 10 POINTS WILL BE GIVEN :)
1) -6y+2=-2(4y+3)
2) 14x-5=7+12x
3) -2(2x-3)=3x
4) -2(x-6)-5=7
5) 2-4(a+1)=8+a
6) 2/7x+6/7=-6/7
NO RUDE COMMENTS 10 POINTS WILL BE GIVEN :)
-
Answers:
1. y = - 4
2. x = 6
3. x = 6/7
4. x = 0
5. a = - 2
6. x = - 6
work:
1. -6y + 2 = -2(4y + 3) distribute the negative 2 to each term in the parentheses
-6y + 2 = -8y - 6 add 8y to both sides
2y + 2 = -6 subtract 2 from both sides
2y = -8 divide both sides by 2
y = -4
2. 14x-5 = 7 + 12x subtract 12x from both sides
2x - 5 = 7 add 5 to both sides
2x = 12 divide both sides by 2
x = 6
3. -2(2x-3) = 3x distribute the -2 to each term in the parentheses
-4x + 6 =3x add 4x to both sides
6 = 7x divide both sides by 7
6/7 = x
4. -2(x-6)-5=7 distribute the -2 to each term in the parentheses
-2x + 12 - 5 = 7 add 2x to both sides
12 - 5 = 7 +2x subtract 7 from both sides
12 - 5 - 7 = 2x simplify the left side
0 = 2x divide both sides by 2
0 = x
5. 2-4(a+1)=8+a distribute the -4 to each term in the parentheses
2 - 4a -4 = 8 + a add 4a to both sides
2 - 4 = 8 + 5a subtract 8 from both sides
2 - 4 - 8 = 5a simplify the left side
-10 = 5a divide both sides by 5
-2 = a
6. 2/7x+6/7=-6/7 multiply both sides by 7
2x + 6 = -6 subtract 6 from both sides
2x = -12 divide both sides by 2
x = -6
1. y = - 4
2. x = 6
3. x = 6/7
4. x = 0
5. a = - 2
6. x = - 6
work:
1. -6y + 2 = -2(4y + 3) distribute the negative 2 to each term in the parentheses
-6y + 2 = -8y - 6 add 8y to both sides
2y + 2 = -6 subtract 2 from both sides
2y = -8 divide both sides by 2
y = -4
2. 14x-5 = 7 + 12x subtract 12x from both sides
2x - 5 = 7 add 5 to both sides
2x = 12 divide both sides by 2
x = 6
3. -2(2x-3) = 3x distribute the -2 to each term in the parentheses
-4x + 6 =3x add 4x to both sides
6 = 7x divide both sides by 7
6/7 = x
4. -2(x-6)-5=7 distribute the -2 to each term in the parentheses
-2x + 12 - 5 = 7 add 2x to both sides
12 - 5 = 7 +2x subtract 7 from both sides
12 - 5 - 7 = 2x simplify the left side
0 = 2x divide both sides by 2
0 = x
5. 2-4(a+1)=8+a distribute the -4 to each term in the parentheses
2 - 4a -4 = 8 + a add 4a to both sides
2 - 4 = 8 + 5a subtract 8 from both sides
2 - 4 - 8 = 5a simplify the left side
-10 = 5a divide both sides by 5
-2 = a
6. 2/7x+6/7=-6/7 multiply both sides by 7
2x + 6 = -6 subtract 6 from both sides
2x = -12 divide both sides by 2
x = -6
-
1) -6y + 2 = -2(4y + 3)
-6y + 2 = -8y - 6
-6y + 8y + 2 = -8y + 8y - 6
2y + 2 = -6
2y + 2 - 2 = -6 - 2
2y = -8
2y/2 = -8/2
y = -4
Solve the others similarly.
-6y + 2 = -8y - 6
-6y + 8y + 2 = -8y + 8y - 6
2y + 2 = -6
2y + 2 - 2 = -6 - 2
2y = -8
2y/2 = -8/2
y = -4
Solve the others similarly.